EFFECT of COMPETENCE, WORK PLACEMENT and ACHIEVEMENT on CAREER DEVELOPMENT (Study at BPN Madiun Municipality ) - Tatik Mulyati; Saraswati Budi Utami (UNIVERSITAS PGRI MADIUN, 2019)
The success of the organization in achieving its goals is supported by internal and external factors. To realize employee career development, the internal side must first receive attention. This study aims to determine the effect of competence, work placement and performance on the career development of employees of the National Land Agency (BPN) of Madiun City.The research method used is quantitative descriptive. The data used are primary data through questionnaires and secondary data. The population in this study were all permanent employees of 40 people. The research variable consists of independent variables, namely competence, work placement and performance, and the dependent variable is employee career development. Variables measured by Likert scale and data analysis techniques using multiple linear regression. Hypothesis testing uses t test and F test. The results of the study concluded that: 1) Competence affects employee career development; 2) Job placement does not affect employee career development; 3) Performance affects the career development of BPN employees in Kota Madiun.Keywords: competence, work placement, work performance, career development